Strategy for Developing Tea Processing Production from Kandis and Gelugur Acid in Sentra Industri Kecil Menengah Garcinia sp in Kabupaten Sijunjung - Gampito, Gampito; Pamel, Rahmi; Ariska, Dwi (Imara: Jurnal Riset Ekonomi Islam, 2024)
Background. The limited production of garci-tea due to various operational constraints,  the process of making tea takes quite a long time, limited electrical power in the factory, In addition, the packaging design of the garci-tea product is similar to that of the competitor's product.Purpose. Knowing how the production strategy that has been implemented by Sentra Industri kecil Menengah (IKM)  Garcinia sp and to develop strategies to improve production that should be implemented Sentra Industri kecil Menengah (IKM) Garcinia sp using the SWOT Analysis MethodMethods. The type of research is Field Research, with a descriptive qualitative approach. The data collection techniques used are through observation, interviews, and documentation. Meanwhile, the data analysis technique uses qualitative analysis with the SWOT method.Results. Sentra Industri kecil Menengah (IKM)  Garcinia sp is the first and only business in Indonesia that processes tea from asam kandis and asam gelugur and has obtained a production permit. In carrying out the production process manually, a 2-shift system is implemented, namely the day shift and the night shift, with different workers for each shift. The production process of IKM Garcinia sp in producing garci-tea products is carried out continuously with stable materials and abundant raw material availability. The product is packaged in the form of tea bags similar to competitors. To make it in another form of packaging, such as ready-to-drink tea in a cup, Sentra Industri kecil Menengah (IKM)  Garcinia sp delayed by the issuance of permits from BPOM.Conclusions. The strategy implemented by Sentra IKM Garcinia sp in increasing its production volume by maximizing working hours and adding more labor. The strategy that should be implemented by Sentra IKM Garcinia sp is using additional tools such as sealing machines, ovens, slicing aids, and utilizing PLN electricity in the production process, updating product packaging to make it more attractive, and leveraging the stable availability of raw materials to continuously increase production capacity to meet consumer demand